Effect of wollastonite addition on sintering of hard porcelain. Issue 4 (May 2015) - Turkmen, O.; Kucuk, A.; Akpinar, S.
Abstract: Hard porcelain body with wollastonite additive was produced by the slip casting method using quartz, potassium feldspar and kaolin raw materials. Wollastonite powders were added to the porcelain formulation by replacing the potassium feldspar up to 5 wt% to explore its effect on the sintering behaviour and also technological properties of as sintered end products. By means of rheological behaviour optimization of ceramic suspensions using several dispersants and sintering enhancement by wollastonite addition, hard porcelain of higher strength at lower firing temperature was obtained. By studying the effect of the additive concentration, on the firing temperatures of the hard porcelain, it is found that reducing firing temperature 25 °C without compromising its quality and thereby producing energy saving was achieved by 1 wt% wollastonite addition.